2022
DOI: 10.36086/jch.v1i1.1113
|View full text |Cite
|
Sign up to set email alerts
|

Relaksasi Self Hipnosis Terhadap Kecemasan Ibu hamil

Abstract: Background: The pregnancy phase there are various kinds of pregnancy problems, one of which is the psychological problem of pregnancy in the form of anxiety. Anxiety can cause negative reactions to pregnant women's conditions such as bleeding, excruciating pain, fear and even the cause of maternal and fetal mortality. Currently many researchers who find a variety of methods that can reduce anxiety non-pharmacologically, namely with the help of self-hypnosisrelaxation. Relaxation  of self hypnosis is a suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The results of Siti Hindun et al's research on self-hypnosis relaxation on the anxiety of pregnant women showed that there was a significant difference between the level of anxiety before and after being given the self-hypnosis relaxation technique, with a p value of 0.000 (12). Winda Martalisa's research in 2013 showed that p = 0.001 (p <0.05) with a correlation coefficient of -689.…”
Section: Discussionmentioning
confidence: 99%
“…The results of Siti Hindun et al's research on self-hypnosis relaxation on the anxiety of pregnant women showed that there was a significant difference between the level of anxiety before and after being given the self-hypnosis relaxation technique, with a p value of 0.000 (12). Winda Martalisa's research in 2013 showed that p = 0.001 (p <0.05) with a correlation coefficient of -689.…”
Section: Discussionmentioning
confidence: 99%